PENGARUH HARGA, PRODUK, DAN PROMOSI TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS PELANGGAN DI PT RETAIL ANIMA PRAKARSA MAKASSAR - Muhammad Haddit Azhizi; Ronald Suryaputra; Tin Agustina Karnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The development of an increasingly competitive business world requires companies to continue to innovate and adapt to rapid changes in customer needs and expectations. This study aims to examine the effect of price, product, and promotion on customer satisfaction and its impact on customer loyalty. With 81 respondents who are active consumers of PT Retail Anima Prakarsa, this study uses the Structural Equation Modeling (SEM) method based on Smart PLS 3 to analyze the Outer and Inner models. The results showed that price and product quality had no significant effect on customer satisfaction, while promotion was shown to have a significant effect on customer satisfaction. In addition, price, product quality, and promotion have no significant effect directly on customer loyalty, but customer satisfaction is found to have a significant effect on customer loyalty. The findings also show that price, product quality, and promotion indirectly have an insignificant effect on customer loyalty through customer satisfaction. These results suggest that although price and product factors have no direct influence on satisfaction or loyalty, companies can increase customer satisfaction through appropriate promotional strategies, which in turn will have a positive impact on customer loyalty. This research provides a theoretical contribution in the development of marketing models in the retail sector.